Predictors of late gadolinium enhancement development and extension in myocardial infarction with non-obstructive coronary arteries. (3rd October 2022) - Amicone, S; Bergamaschi, L; Armillotta, M; Sansonetti, A; Stefanizzi, A; Impellizzeri, A; Suma, N; Tattilo, F P; Angeli, F; Paolisso, P; Rinaldi, A; Foa', A; et al.
Abstract: Background: Myocardial infarction with non-obstructive coronary arteries (MINOCA) is a heterogeneous clinical entity and in its complex diagnostic approach cardiovascular magnetic resonance (CMR) plays a pivotal role. Purpose: To characterize the differences of MINOCA patients with and without late gadolinium enhancement (LGE) at CMR and to identify the predictors for ischemic LGE development and extension. Methods: We assessed 461 MINOCA cases from January 2016 to June 2021. MINOCA were defined according to the current European guidelines criteria. We excluded acute myocarditis, Tako-tsubo syndromes, cardiomyopathies, or non-pathological CMR. According to CMR imaging findings, our cohort was divided into two CMR phenotypes based on regional myocardial necrosis detected throughout LGE ("LGE-positive MINOCA") or regional ischemic injury without LGE ("LGE-negative MINOCA"). Extended LGE was considered as the presence of >2 segments with transmural LGE. Multivariate logistic regression analysis was used to determine the predictors of LGE and extended LGE. Results: The final cohort included 175 MINOCA: 121 (69.1%) constituted the LGE-positive group. The mean time delay between acute clinical presentation and CMR was 6±2.9 days. At admission MINOCA LGE-patients more frequently presented angina and ST segment elevation (24% vs 7.4%, p=0.01), compared to LGE negative ones. Furthermore, the LGE positive group had a significantly greater infarct size, measured by peak hs-Troponin I values and left ventricular function (LVEF). The only predictor of LGE was the peak troponin value (OR 1.64, 95% CI 1.18–2.28, p=0.003), while predictors of extended LGE were ST-segment elevation at admission (OR 7.44, 95% CI 1.57–35.22, p=0.01), peak troponin values (OR 1.07, 95% CI 1.02–1.13, p=0.01) and the presence of non-obstructive coronary artery disease at coronary angiography (OR 5.49, 95% CI 1.20–25.09, p=0.028). Conclusion: The presence and extension of LGE at early CMR evaluation is an important feature in the setting of MINOCA. In addition, simple baseline characteristics (such as ST elevation, peak troponin value and LVEF) may aid the identification of a greater ischemic necrosis burden at CMR and therefore these high-risk MINOCA subjects could be benefit from a stricter management effort. Funding Acknowledgement: Type of funding sources: None.